2016
DOI: 10.1513/annalsats.201512-806oc
|View full text |Cite
|
Sign up to set email alerts
|

Lung Transplant Outcomes in Systemic Sclerosis with Significant Esophageal Dysfunction. A Comprehensive Single-Center Experience

Abstract: Relative to other lung transplant indications, our SSc group experienced comparable survival, primary graft dysfunction, acute rejection, bronchiolitis obliterans syndrome, and microbiology of respiratory isolates, despite the high prevalence of severe esophageal dysfunction. Esophageal dysfunction rarely precluded active listing for lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 27 publications
0
53
0
1
Order By: Relevance
“…Deemed a last-resort intervention for patients with end-stage lung disease, lung transplantation is presently performed at select transplantation centers for patients with SSc. The literature in this area is evolving, and although a retrospective cohort study found a 48% increase in the 1-year mortality rate among patients with SSc undergoing lung transplantation in the United States compared with those with non-SSc-ILD (100), other studies have not found any difference in survival after lung transplantation between patients with SSc and non-SSc patients with fibrotic lung diseases (101)(102)(103)(104). Factors associated with higher mortality in patients with SSc-ILD undergoing lung transplantation include older age (104) and elevated body mass index (103).…”
Section: Lung Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…Deemed a last-resort intervention for patients with end-stage lung disease, lung transplantation is presently performed at select transplantation centers for patients with SSc. The literature in this area is evolving, and although a retrospective cohort study found a 48% increase in the 1-year mortality rate among patients with SSc undergoing lung transplantation in the United States compared with those with non-SSc-ILD (100), other studies have not found any difference in survival after lung transplantation between patients with SSc and non-SSc patients with fibrotic lung diseases (101)(102)(103)(104). Factors associated with higher mortality in patients with SSc-ILD undergoing lung transplantation include older age (104) and elevated body mass index (103).…”
Section: Lung Transplantationmentioning
confidence: 99%
“…The literature in this area is evolving, and although a retrospective cohort study found a 48% increase in the 1-year mortality rate among patients with SSc undergoing lung transplantation in the United States compared with those with non-SSc-ILD (100), other studies have not found any difference in survival after lung transplantation between patients with SSc and non-SSc patients with fibrotic lung diseases (101)(102)(103)(104). Factors associated with higher mortality in patients with SSc-ILD undergoing lung transplantation include older age (104) and elevated body mass index (103). However, contrary to previous thought, severity of esophageal dysfunction by either morphometry or manometry criteria was not associated with survival in patients with SSc-ILD (n = 35) who underwent lung transplantation at a single center (104).…”
Section: Lung Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of lung transplantation in patients with SSc requires discussion due to concerns over whether esophageal dysfunction and gastro-esophageal reflux may cause damage to the transplanted lung, and whether the multimorbidity of patients with SSc will impact outcomes. However, recent data suggest that post-transplant outcomes, including graft dysfunction and survival, are similar in selected patients with SSc-ILD as in those with other types of ILD [47][48][49].…”
Section: Lung Transplantationmentioning
confidence: 99%
“…Miele and colleagues from the University of California at Los Angeles (UCLA) Lung Transplantation Program report their experience in 35 patients with SSc-ILD who underwent lung transplant between 2000 and 2012 (14). In addition to comparing outcomes to patients with diffuse fibrotic lung disease, the authors compared outcomes to all other lung transplant indications combined and to a 4:1 matched cohort based on age, lung allocation score, transplant type, and presence of pulmonary hypertension.…”
mentioning
confidence: 99%